2021
DOI: 10.1186/s12884-021-03955-7
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section defects may affect pregnancy outcomes after in vitro fertilization-embryo transfer: a retrospective study

Abstract: Background Caesarean section rates are rising worldwide. One adverse effect of caesarean section reported in some studies is an increased risk of subfertility. Only a few studies have assessed the relationship between the previous mode of delivery and in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) reproductive outcomes. In this study, we primarily investigated the impact of a history of caesarean section with or without defects on IVF/ICSI-ET outcomes comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Patients with CSD were associated with a significantly lower rate of subsequent live birth (aOR: 0.609, 95%CI: 0.476~0.778, P <0.001) and clinical pregnancy (aOR: 0.779, 95%CI: 0.623~0.973, P =0.027), as well as a higher likelihood of miscarriage (aOR:1.407, 95%CI: 1.03~1.923, P =0.032) compared with those without defect at the site of the cesarean incision. The results were in agreement with previous studies ( 21 , 35 ). The existence of CSD could lead to poor pregnancy outcomes in patients undergoing IVF.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Patients with CSD were associated with a significantly lower rate of subsequent live birth (aOR: 0.609, 95%CI: 0.476~0.778, P <0.001) and clinical pregnancy (aOR: 0.779, 95%CI: 0.623~0.973, P =0.027), as well as a higher likelihood of miscarriage (aOR:1.407, 95%CI: 1.03~1.923, P =0.032) compared with those without defect at the site of the cesarean incision. The results were in agreement with previous studies ( 21 , 35 ). The existence of CSD could lead to poor pregnancy outcomes in patients undergoing IVF.…”
Section: Discussionsupporting
confidence: 94%
“…( 20 ) observed no difference in live birth rate (40.59% vs 45.38%, P =0.466) between the CD and VD groups, however, there was imbalanced maternal age. Diao ( 21 ) et al. also revealed no significant difference in live birth rate (33.1% vs36.4%, OR: 0.86, 95%CI: 0.64~1.16, P >0.05) with thinner endometrial thickness in the CD group.…”
Section: Discussionmentioning
confidence: 92%
“…With the increasing cesarean rate, the consequences of the mode of delivery on fertility is a more striking issue, and some studies have suggested that cesarean section may cause negative reproductive outcomes (7)(8)(9). However, some studies suggest that there was no such relationship (10,11,22).…”
Section: Discussionmentioning
confidence: 99%
“…While the rate predicted by the World Health Organization for cesarean section was between 10% and 15% in the 1980s, it is over 40% in some regions today (6). Today, the increasing frequency of cesarean section raises concerns with the studies showing some negative effects on fertility (7)(8)(9). However, these studies had limitations, such as the older age of the cesarean section group, the co-morbidities of the cesarean section group, and the non-homogeneous distribution of the groups (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that CD without defects does not decrease the live birth rate after IVF compared with previous VD. However, the presence of CSD in women, especially young women (age ≤ 35 years), significantly impairs the chances of subsequent pregnancy in patients undergoing IVF-ET [ 13 ]. The effect of CD on IVF pregnancy outcomes is uncertain and only a few studies to date have evaluated the association between CD/CSD and frozen-thawed embryo transfer (FET) pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%